Psychoactive substance use and associated factors among Mohammed first university students, Oujda, Morocco: a cross-sectional study - Adil Essadi; Hanane Aissaoui; Asmae Yeznasni; Asmae Lekfif; Sanae Sebbar; Mariam Atassi; Naima Abda (BMC, 2024)
Abstract Background The use of psychoactive substances, including tobacco, alcohol, and others, remains a major public health problem. However, few studies have been conducted on Moroccan university students. This study aimed to assess the prevalence and associated factors of substance use among students at Mohammed First University, Oujda, Morocco. Methods We conducted this cross-sectional study with students enrolled at one of the Mohammed First University of Oujda's institutes as part of the 2021-202 academic year. We used a self-administered survey to collect data anonymously. We cleaned the data and then entered it into IBM SPSS Statistics 21 for analysis. Data analysis involved descriptive statistics as well as univariate and multivariate analysis. We considered a P value < 0.05 as the level of significance. Results In this study, out of 500 students we asked to complete the survey, 478 responded; the response rate was 95.6%. The average age was 21.1 ± 3.0, and the M/F sex ratio was 0.97. The lifetime prevalence of psychoactive substance use among Oujda University students was 28.7%. The most commonly used substances were tobacco (24.1%), alcohol (15.9%), cannabis (13.4%), sedatives (6.9%), stimulants (5.2%), and cocaine (4.4%). Male sex, age > 20 years, self-financing, school failure (one year repeated or more), the practice of a leisure activity, the presence of a personal medical or psychiatric history, and the presence of a family medical history were all significantly associated with the use of psychoactive substances. Conclusion Our study revealed a significant prevalence of psychoactive substance use among university students in Oujda, highlighting the need for interventions at various levels. Further analytical studies are necessary to better understand the initiation and maintenance of psychoactive substance use and to identify all associated factors to enhance prevention strategies against substance use disorders.